Changes in interaction network topology and species composition of flower‐visiting insects across three land use types. (29th June 2018) - Adedoja, Opeyemi; Kehinde, Temitope
Abstract: Land use change is a leading factor in the cause of pollinator decline globally. The response of flower‐visiting insects to habitat transformation and disturbance has been well studied. However, the effect of these anthropogenic disturbances on the structure of insect–flower interaction networks is not well known. We examined how insect–flower interaction network topology changes across land use types with varying levels of disturbance. Three replicates of agricultural lands, grasslands and secondary forest habitats were sampled on a monthly basis for 12 months. The highest mean abundance of flower‐visiting insects and flowering plants was observed in the secondary forest and the lowest record was found on agricultural lands. Furthermore, networks in secondary forests had a higher mean number of interactions, network size and nestedness compared to those observed in agricultural fields. Flower abundance was positively correlated with the number of interactions and network specialization. The significantly higher value of the qualitative and quantitative network indices in the secondary forests underscores the ecological importance of this land use type for conservation of insect–flower interactions in highly fragmented landscapes in the tropics such as the one studied here. Conservation efforts should concentrate on increasing the abundance of floral resources as changes in important network indices were mediated by flower abundance across the land use types.